2020
DOI: 10.1200/jop.19.00470
|View full text |Cite
|
Sign up to set email alerts
|

Oncologist Burnout Syndrome in Eastern Europe: Results of the Multinational Survey

Abstract: PURPOSE: Burnout is defined as a three-dimensional syndrome—emotional exhaustion (EE), depersonalization (DP), and reduced personal accomplishment (PA)—caused by chronic occupational stress. The aim of the current study was to investigate the prevalence of burnout among oncologists in Eastern Europe and to identify the contributing factors. METHODS: The study was conducted as an online survey between October 2017 and March 2018. Oncologists (including medical, radiation, clinical, and surgical oncologists) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
(34 reference statements)
1
14
1
4
Order By: Relevance
“…Ramey et al (2017) acordaron el trabajar más de 60 horas semanales y la necesidad de acudir a uno o más días durante el fin de semana por semana de guardia. Finalmente, en el estudio de Kust et al (2022) manifestaron una EE alta de 44%, una D alta de 28,7% y una PA baja de 47,3%.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Ramey et al (2017) acordaron el trabajar más de 60 horas semanales y la necesidad de acudir a uno o más días durante el fin de semana por semana de guardia. Finalmente, en el estudio de Kust et al (2022) manifestaron una EE alta de 44%, una D alta de 28,7% y una PA baja de 47,3%.…”
Section: Resultados Y Discusiónunclassified
“…establecieron una EE alta de 28,3%, una D alta de 17,1% y una PA baja de 12%. Finalmente, en el estudio deKust et al (2022) manifestaron una EE alta de 44%, una D alta de 28,7% y una PA baja de 47,3%, porcentajes que no han tenido mucha variación en relación con los estudios ya mencionados.Los factores de riesgo relacionados con el Síndrome de Burnout tuvieron variaciones con cada publicación, para De la Fuente et al (2020), los factores de riesgo fueron: falta de experiencia laboral, enfermeras jóvenes, mayor nivel de experiencia laboral, turnos nocturnos, exceso de trabajo, chismes de los compañeros, no tener hijos, género femenino, enfermeras mayores de 40 años y problemas de salud. Estos factores se relacionan con el estudiode Yates & Samuel (2019) en donde se indica la carga laboral excesiva y el elevado número de pacientes, sobresale el factor: falta de conciliación de la vida laboral y familiar.…”
unclassified
“…As many as 85% of oncologists affirmed that they had experienced greater burnout during, compared to before the pandemic, while 86% showed moderate to high levels of burnout on the OLBI. In a pre-pandemic study of burnout among oncologists in Eastern Europe during 2019, Kust et al found that 71% of the sample (including Croatian oncologists) experienced high burnout [35]. Although Kust et al used a different method to us (the Maslach Burnout Inventory), both studies find a high percentage of oncologists with burnout symptoms and an increased level of burnout in Croatian oncologists during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Na Europa Oriental, a taxa de esgotamento mental, em especial o relacionado ao trabalho entre os oncologistas, é alta e os oncologistas mais jovens são os mais vulneráveis a ela 68 . Marijanović et al 38 afirmam que prestar serviços de oncologia durante uma pandemia contribuiu ainda mais para os desafios da saúde mental entre os profissionais de saúde.…”
Section: Discussionunclassified